2021
DOI: 10.55230/mabjournal.v50i2.2159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Training and Behavioural Strategies Towards Muscle Strength and Mental Health in the Elderly

Abstract: The promotion of physical training (PT) and positive behavior in the elderly requires effective interventions. This study shows the effect of PT during an 11-week intervention program by applying behavioral strategies. A total of 63 participants aged 65 years old were randomly divided into three groups: Physical with a behavioral group, PB (n=18), Physical group, PG (n=23), and Control group, CG (n=22). PB and PG participants underwent a six-week group-based multi-component PT for one hour per session, three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…The studies concluded that chair-based exercise programs have positive effects on physical and cognitive functioning in older adults, thus improving their physical and mental well-being. Upper and lower limb: Two of the studies conducted quasiexperimental studies [67,138], one conducted randomized controlled intervention [137], one conducted a randomized controlled pilot trial [14], and the others didn't mention the study conducted. Two of the studies included only female participants [67,130], and one included only male participants [37].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies concluded that chair-based exercise programs have positive effects on physical and cognitive functioning in older adults, thus improving their physical and mental well-being. Upper and lower limb: Two of the studies conducted quasiexperimental studies [67,138], one conducted randomized controlled intervention [137], one conducted a randomized controlled pilot trial [14], and the others didn't mention the study conducted. Two of the studies included only female participants [67,130], and one included only male participants [37].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The number of participants ranged from 20 to 63. Two of the studies were conducted in England [14,130], one was conducted in South Korea [137], one in Malaysia [138], and one in Brazil [139]. The study [67] concluded that chair yoga improves upper and lower limb strength.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Previous studies have demonstrated a close relationship between physical fitness and mental symptoms. For example, exercise improves mood [ 18 ], running can lessen loneliness and improve one’s physical well-being [ 19 , 20 ], and eight weeks of swimming instruction can help college students feel better mentally [ 21 ]. However, exercise regimens in these studies must provide a comprehensive assessment of a person’s level of physical fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Dennison et al emphasize that while overweight individuals are at higher risk of diabetes, the onset can be forestalled with awareness, exercise, and a healthy lifestyle geared towards weight loss and blood sugar reduction. However, in this fastpaced era, many people indulge in unhealthy habits, such as consuming sugary or unhealthy foods, smoking, drinking alcohol, and avoiding exercise, as preliminary research indicates [16]. Neglecting these habits may have dire consequences, hastening the onset of severe complications [17].…”
Section: Introductionmentioning
confidence: 99%